FIVE MAXIMA OF BIODIVERSITY IN THE PALEOZOIC OF CENTRAL ASIA - Leleshus V.L. (My University, 2003)
Five maxima of biodiversity are identified in the Paleozoic of Central Asia: Late Cambrian, Caradoc-Ashgill, Early Devonian, Early Carboniferous, and late Early Permian. These maxima regularly alternated with the minima of biodiversity in the Early Ordovician, Early Silurian, Late Devonian, Middle Carboniferous, and Early Triassic.
Keywords: Paleozoic; Paleozoic; Палеозой